2020
DOI: 10.25122/jml-2019-0105
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Music Therapy and Aromatherapy with Chamomile-Lavender Essential Oil on the Anxiety of Clinical Nurses: A Randomized and Double-Blind Clinical Trial

Abstract: Nurses may be anxious due to critical and emergencies, and anxiety can affect their professional performance. Non-pharmacological interventions, as a safe method, can reduce anxiety. This study aimed to determine the effect of music therapy and aromatherapy with chamomile - lavender essential oil on the anxiety of clinical nurses. This was a randomized, double-blind clinical trial. One hundred twenty nurses from clinical wards of Besat Hospital in Sanandaj, Iran, were selected between 2018 and 2019 by purposef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 25 publications
1
11
0
2
Order By: Relevance
“…The results of a RCT showed that chamomile-lavender aromatherapy decreased the anxiety of nurses compared to the control group. 58 In another study, it was reported that the inhalation of chamomile essential oil reduced patients’ anxiety before endoscopy. 59 Furthermore, it was found in a study that inhalation aromatherapy using chamomile essential oils reduced depression and anxiety levels in community-dwelling older adults.…”
Section: Discussionmentioning
confidence: 99%
“…The results of a RCT showed that chamomile-lavender aromatherapy decreased the anxiety of nurses compared to the control group. 58 In another study, it was reported that the inhalation of chamomile essential oil reduced patients’ anxiety before endoscopy. 59 Furthermore, it was found in a study that inhalation aromatherapy using chamomile essential oils reduced depression and anxiety levels in community-dwelling older adults.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Melissa officinalis L. (lemon balm) EO was tested in acute coronary syndrome (ACS) patients, resulting in significantly reduced scores of stress and anxiety, with reduced heart rate ( p < 0.001) along with remarkable decrease in the mean arterial pressure in the Melissa group compared to the placebo group ( p < 0.001) [ 176 ]. Lavandula angustifolia L. (lavender) EO was tested for 4 weeks on patients with insomnia, showing significantly improved sleep quality and duration, improved quality of life, and improved overall mood [ 178 ], while the combination of lavender with chamomile ( Matricaria recutita ) showed statistically significant improvement in depression, anxiety, and stress levels immediately and one month after the intervention in the lavender and chamomile group compared to the control group ( p < 0.01) [ 171 ]. Similarly, lavender combined with Roman chamomile ( Anthemis nobilis ) and neroli ( Citrus aurantium flowers EO) showed reduced anxiety and improved sleep quality [ 181 ].…”
Section: Essential Oils For Neuroprotection and Modulation Of Mood An...mentioning
confidence: 99%
“…[12] Another study recommended music therapy and aromatherapy with chamomile and lavender essential oils in combination to reduce the nurses anxiety in the clinical setting. [13] The combination of clomipramine and inhaled Roman chamomile essential oil attenuated depression-like behavior in mice tested for forced swimming. Meanwhile, inhalation of the essential oil of Roman chamomile improved the antidepressant effect of clomipramine by increasing hippocampal neurogenesis and regulating corticosterone levels in patients with treatment-resistant depression.…”
Section: Introductionmentioning
confidence: 99%
“…A parallel randomized controlled clinical trial study found that inhaled aromatherapy with essential oils of lavender and chamomile helped reduce depression, anxiety and stress in elderly people in the community [12] . Another study recommended music therapy and aromatherapy with chamomile and lavender essential oils in combination to reduce the nurses anxiety in the clinical setting [13] . The combination of clomipramine and inhaled Roman chamomile essential oil attenuated depression‐like behavior in mice tested for forced swimming.…”
Section: Introductionmentioning
confidence: 99%